Literary criticisms of law - Binder, Guyora; Weisberg, Robert, 1946- (Princeton, N.J. : Princeton University Press, 2000)
In this book, the first to offer a comprehensive examination of the emerging study of law as literature, Guyora Binder and Robert Weisberg show that law is not only a scheme of social order, but also a process of creating meaning, and a crucial dimension of modern culture. They present lawyers as literary innovators, who creatively interpret legal authority, narrate disputed facts and hypothetical fictions, represent persons before the law, move audiences with artful rhetoric, and invent new legal forms and concepts. Binder and Weisberg explain the literary theories and methods increasingly applied to law, and they introduce and synthesize the work of over a hundred authors in the fields of law, literature, philosophy, and cultural studies. Drawing on these disparate bodies of scholarship, Binder and Weisberg analyze law as interpretation, narration, rhetoric, language, and culture, placing each of these approaches within the history of literary and legal thought. They sort the styles of analysis most likely to sharpen critical understanding from those that risk self-indulgent sentimentalism or sterile skepticism, and they endorse a broadly synthetic cultural criticism that views law as an arena for composing and contesting identity, status, and character. Such a cultural criticism would evaluate law not simply as a device for realizing rights and interests but also as the framework for a vibrant cultural life.
Cover13; -- Contents13; -- PREFACE -- INTRODUCTION Law as Literature -- From Letters to Literature -- Literary Canons and Academies -- The Risks and Possibilities of Law and Literature -- Genres of Criticism -- CHAPTER ONE Interpretive Crises in American Legal Thought -- Introduction -- 1.1 The Crisis of Whig Hermeneutics -- 1.2 Progressive Interpretation -- 1.3 The Crisis of Progressive Interpretation -- Conclusion -- CHAPTER TWO Hermeneutic Criticism of Law -- Introduction -- 2.1 Literary Theories of Interpretation -- 2.2 Law as Literary Interpretation -- 2.3 Legal Hermeneutics in Practice -- Conclusion -- CHAPTER THREE Narrative Criticism of Law -- Introduction: The Law as Narrative Trope -- 3.1 Literary Theories of Narrative -- 3.2 Instrumental Claims: Narrative as Laws Antagonist and Salvation -- 3.3 Law and Narrative as Mutually Inherent -- Conclusion: Performing the Law and Narrating the Nation -- CHAPTER FOUR Rhetorical Criticism of Law -- Introduction: Law, Rhetoric, and the Problem of Authoritarianism -- 4.1 A Very Brief History of Rhetoric -- 4.2 The Conservative Model of Rhetoric -- 4.3 Is a Liberal Rhetoric Possible? -- Conclusion -- CHAPTER FIVE Deconstructive Criticism of Law -- Introduction -- 5.1 Derridean Deconstruction -- 5.2 Deconstruction as Epistemological Criticism -- 5.3 Deconstruction as Ethical Criticism -- Conclusion -- CHAPTER SIX Cultural Criticism of Law -- Introduction -- 6.1 Theoretical Sources for Cultural Criticism of Law -- 6.2 Cultural Readings of Disputes -- 6.3 Cultural Readings of Capitalism -- Conclusion -- INDEX.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Law and literature; Culture and law; Law -- Interpretation and construction; Literature -- History and criticism; Droit et littérature.; Culture et droit; Droit -- Interprétation.; Littérature -- Histoire et critique; LAW -- Jurisprudence; LAW -- General Practice; LAW -- Reference; LAW -- Essays; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; Culture and law; Law and literature; Law -- Interpretation and construction; Literature; Electronic books; Criticism, interpretation, etc